Variation in stroke care at the hospital level: A cross-sectional multicenter study - Lens, Charlotte; Coeckelberghs, Ellen; Seys, Deborah; Demeestere, Jelle; Weltens, Caroline; Vanhaecht, Kris; Lemmens, Robin (Frontiers in Neurology, 2022)
Introduction: Stroke is one of the leading causes of mortality and disability. Improving patient outcomes can be achieved by improving stroke care and adherence to guidelines. Since wide variation in adherence rates for stroke guidelines still exists, we aimed to describe and compare stroke care variability within Belgian hospitals. Materials and Methods: An observational, multicentre study was performed in 29 Belgian hospitals. We retrospectively collected patient characteristics, quality indicators and time metrics from the last 30 consecutive patients per hospital, diagnosed with ischemic stroke in 2019 with structured questionnaires. Mean adherence ratios (%) ± SD [minimum – maximum] were calculated. Results: We analysed 870 patient records from 29 hospitals. Results showed large inter- and intra-hospitals variations in adherence for various indicators. Almost all patients received brain imaging (99.7%) followed by admission at a stroke unit in 82.9%. Of patients not receiving thrombolysis, 92.5% were started on antithrombotic drugs. Indicators with moderate median adherence but large inter-hospital variability were glycaemia monitoring (82.3% ± 16.7% [26.7% - 100.0%]), performing clinical neurological examination and documentation of stroke severity (63.1% ± 36.8% [0% - 100%]); and screening for activities of daily living (51.1% ± 40,3% [0.0% - 100.0%]). Other indicators lacked adequate adherence: swallowing function screening (37.0% ± 30.4%, [0.0% - 93.3%]), depression screening (20.2% ± 35.8% [0.0% - 100%]) and timely body temperature measurement (15.1% ± 17.0% [0.0% - 60%]). Conclusion: We identified high adherence to guidelines for some indicators, but lower rates with large inter-hospital variability for other recommendations also based on robust evidence. Improvement strategies should be implemented to improve the latter.